Theoretical and experimental study of erbium-doped fiber laser chaotic conditions in response to acoustic vibrations for pipe leakage monitoring - Onubogu, Nneka Obianuju (2023)
Pipelines undergo deformation leading to leakage several times throughout their service life. Hence, there is a need for Structural Health Monitoring (SHM) to ensure the safety of pipelines. Various conventional SHM and fiber optics technology methods for pipeline leakage detection have been explored in the past, most of which are expensive; have slow response time; limited coverage, and limited sensitivity. This thesis presents a costeffective and highly sensitive Erbium-doped fiber laser (EDFL) sensor that was designed and tested for its effectiveness in pipeline leakage and location detection. Results obtained showed an overall sensor accuracy of 90 % for leak location detection. However, during the tests, some instabilities were observed in the sensor. This led to the experimental and theoretical study of the behavior (including chaotic conditions) of the modulated EDFL to understand the cause of the instabilities. Two EDFL configurations (linear cavity – EDFLL and ring cavity – EDFRL) both under pump and external cavity-loss modulations were analyzed experimentally and theoretically. The bifurcation diagrams obtained showed resonance peaks, regions of chaos, and optical bi-stability confirming that the existence of bifurcation is the root cause of the EDFL's unstable behavior. For the theoretical analysis, a modified model built from two rate equations of a class B laser was presented. The model generates all spectral characteristics obtained during experimental pump and external cavity-loss modulations of the two EDFL configurations and can therefore be used to quickly predict the results of the EDFL sensor for further improvement in the future. It has been proven that the dynamic response of the pump-modulated EDFLL and EDFRL can be theoretically predicted with total average accuracies of: 91.09 % (EDFLL) and 86.60 % (EDFRL) in terms of the “resonance peaks”; and 91.58 % (EDFLL) and 90.79 % (EDFRL) in terms of the “frequency after which saturation occurred”. Similarly, it has been proven that the dynamic response of the cavity-loss modulated EDFLL and EDFRL can be theoretically predicted with total average accuracies of: 91.04 % (EDFLL) and 91.07 % (EDFRL) in terms of the “resonance peaks”; and 91.70 % (EDFLL) and 95.96 % (EDFRL) in terms of the “frequency after which saturation” occurred. The EDFLL and the EDFRL are highly sensitive to external perturbations such as acoustic waves even at low frequencies ranging from 100 Hz to 100 kHz and can be used for pipeline monitoring.